2003
DOI: 10.1128/jb.185.20.6199-6204.2003
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Water Availability Influences the Dynamics, Development, and Ultrastructural Properties of Pseudomonas putida Biofilms

Abstract: Pseudomonas putida strain mt-2 unsaturated biofilm formation proceeds through three distinct developmental phases, culminating in the formation of a microcolony. The form and severity of reduced water availability alter cell morphology, which influences microcolony size and ultrastructure. The dehydration (matric stress) treatments resulted in biofilms comprised of smaller cells, but they were taller and more porous and had a thicker extracellular polysaccharide layer at the air interface. In the solute stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 35 publications
1
83
0
Order By: Relevance
“…Hydration status and pore-space characteristics are critical factors shaping nutrient fields and bacterial motility, and are thus key to understanding bacterial interactions in soil and other porous media such as dry food products (Barton and Ford, 1997;Dens and Van Impe, 2000;Wilson et al, 2002;Chang and Halverson, 2003;Or et al, 2007;Chen and Jin, 2011). Although motility has long been argued as a key factor for survival in heterogeneous environments and for biodiversity maintenance (Fenchel, 2002;Reichenbach et al, 2007;Vos and Velicer, 2008), it is only recently that crucial processes regulating bacterial motility within liquid films forming on partially hydrated rough surfaces have been quantified (Dechesne et al, 2010;Wang and Or, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hydration status and pore-space characteristics are critical factors shaping nutrient fields and bacterial motility, and are thus key to understanding bacterial interactions in soil and other porous media such as dry food products (Barton and Ford, 1997;Dens and Van Impe, 2000;Wilson et al, 2002;Chang and Halverson, 2003;Or et al, 2007;Chen and Jin, 2011). Although motility has long been argued as a key factor for survival in heterogeneous environments and for biodiversity maintenance (Fenchel, 2002;Reichenbach et al, 2007;Vos and Velicer, 2008), it is only recently that crucial processes regulating bacterial motility within liquid films forming on partially hydrated rough surfaces have been quantified (Dechesne et al, 2010;Wang and Or, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This orientation probably provides more surface area for cells to efficiently take up the p-cresol vapour and minerals from the agar surface. A similar arrangement of cells has been observed in the early stages of microcolony development by Escherichia coli and Pseudomonas putida (Chang & Halverson, 2003;Shapiro & Hsu, 1989). When the SAA were in actively growing stages, most long cells, including Y-shaped cells, were twisted in upright positions.…”
Section: Discussionmentioning
confidence: 54%
“…2C2). Perpendicular cell arrangements have been observed in other multicellular structures, including colonies and biofilms (Chang & Halverson, 2003;Enos-Berlage & McCarter, 2000;Lee & Veeranagouda, 2009). Closer examination of the images of the stalk of the SAA revealed that the short rod cells that were less than 1 mm in diameter had a more regularly compact arrangement (Fig.…”
Section: Sem Observations Of Saamentioning
confidence: 99%
“…Thus, favorable conditions should be provided to facilitate the formation of biofilm in practice. As indicated by Chang and Halverson (2003), the formation of rhizosphere bacterial biofilm is mainly affected by water moisture, nutritional status and environmental parameters.…”
Section: Obstacles To the Long-term Colonization Of Antagonists: The mentioning
confidence: 99%